All Days 2008
DOI: 10.2118/116029-ms
|View full text |Cite
|
Sign up to set email alerts
|

Drillpipe Stress Distribution and Cumulative Fatigue Analysis in Complex Well Drilling: New Approach in Fatigue Optimization

Abstract: In the today high-cost and complex drilling environment, the importance of drillstring failure issue has dramatically reappeared, in spite of many manufacturing and materials improvements. Most drillstring failures are due to fatigue, resulting from repeated cyclic bending loads and stresses in tensile or buckled drill pipes. Fatigue prediction is usually based on the cumulative fatigue damage model from Hansford and Lubinski as defined in API RP7G. This model, based on S-N curves, a failure criterion and a da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In any case, the success of the lifting operations depends on the results of inclinometry and the accuracy of evaluation the influence of the profile of certain intervals of the well on the features of the formation of the PU stressstrain state based on their design. The possibility of using modern software products to study the stress-strain state of pipe columns is indicated in publications [1,15]. In [19], the results of modeling the deformed state of a drill pipe string using the finite element method are presented.…”
Section: Substantiation Of the Need For Evaluation Of The Stress-stramentioning
confidence: 99%
“…In any case, the success of the lifting operations depends on the results of inclinometry and the accuracy of evaluation the influence of the profile of certain intervals of the well on the features of the formation of the PU stressstrain state based on their design. The possibility of using modern software products to study the stress-strain state of pipe columns is indicated in publications [1,15]. In [19], the results of modeling the deformed state of a drill pipe string using the finite element method are presented.…”
Section: Substantiation Of the Need For Evaluation Of The Stress-stramentioning
confidence: 99%
“…Similar studies are performed in [3,4]. For approximation of fatigue curves, power two-parameter equations are used.…”
Section: Research Of Existing Solutions Of the Problemmentioning
confidence: 99%
“…The problem is solved in both flat and spatial formulation [3,4]. But in the publication [5], special software based on the finite element method is used to analyze the stress-strain state of the drill string. However, it should be remembered that with an increase in compliance of the mathematical model with a real object, the equations for its description become significantly more complicated.…”
Section: Research Of Existing Solutions Of the Problemmentioning
confidence: 99%
“…In order to determine the coefficients of the function (4), the data from Tables 4, 5 has been converted to the following form (Tables 8,9). At the same time, it has been taken into account that laboratory tests are carried out at the price of dividing the tensile testing machine 80 N. As a result, the approximation of the data from the Tables 8, 9, the function (4) acquired the form for the first and second stages of calibration, respectively: Graphically, the data from the Tables 8, 9, and also functions (5) and (6) are shown in Fig. 10.…”
Section: Issn 2226-3780mentioning
confidence: 99%